ANALISIS PENERAPAN PSAK 72 (SEWA) PADA PERUSAHAAN LOGISTIK DI INDONESIA - Salihi, Said Saleh (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
This study aims to analyze the level of compliance and the quality of implementation of PSAK 72 (Leases) in logistics companies listed. Effective from January 1, 2020, PSAK 72 introduced significant changes, primarily the elimina tion of operating lease classification and the mandatory recognition of right-of-use assets and lease liabilities for almost all long-term lease contracts. The research employs a descriptive qualitative approach with content analysis methods applied to the financial statements and notes to the financial statements. The results show variation in the level of compliance and quality of implementation. Most companies have recogn ized Right-of-Use (RoU) Assets and Lease Liabilities in accordance with the provisions. However, significant differ ences were found in the qua lity of disclosures, particularly concerning key assumptions (discount rate), explanations of the transition impact, and details of future lease commitments. This study concludes that alth ough basic technical compliance is achieved, there is significant room for improvement in the depth and clarity of disclosures, as well as in the consistency of applying critical assumptions. These findings provide valuable input for regu lators, financial statement preparers, auditors, and financial statement users in evaluating the impact of PSAK 72 in this strategic sector.